Evaluation of the in vitro stability of direct oral anticoagulants in blood samples under different storage conditions. (1st October 2021) - Thuile, Katharina; Giacomuzzi, Katia; Jani, Erika; Marschang, Peter; Mueller, Thomas
Abstract: In this study, we evaluated the in vitro stability of direct oral anticoagulants (DOACs) in blood samples of 57 patients under different storage conditions using functional coagulation assays. We determined the analyte concentrations (1) immediately after blood collection (baseline); (2) after storage of citrated whole blood (agitated) at room temperature and citrated plasma at room temperature and at 4 °C for 4, 8, and 24 h, respectively; and (3) after storage of citrated plasma at −20 °C for 30, 60, and 90 days. According to the concept of acceptable change limits (ACL), analytes were considered stable if the mean relative analyte recovery at a given time was >78%. The mean baseline values (range) of dabigatran, rivaroxaban, apixaban, and edoxaban were 115 ng/mL (62–217), 129 ng/mL (31–215), 156 ng/mL (49–362), and 101 ng/mL (33–283), respectively. After applying the analyte stability limit, all four DOACs were stable for 24 h at room temperature and at 4 °C. The mean recovery after 24 h was 102–111% for dabigatran, 88–97% for rivaroxaban, 95–98% for apixaban, and 90–96% for edoxaban. When plasma samples were stored at −20 °C, the mean percentage deviation after 90 days for all four DOACs was ≤10%, even after three freeze-thaw cycles. Thus, for the correct determination of DOAC plasma concentrations, blood samples do not have to be analyzed immediately and can be stored at room temperature for up to 24 h before analysis. In clinical practice, blood sample transport and storage for DOAC measurements appear to be unproblematic.